Horseback Riding and Cavalry in Mycenaean Greece - Kelder, J (Peeters Online Journals, 2012)
This paper evaluates the evidence for horseback riding in Mycenaean Greece. This paper argues that horseback riding, which is widely held to be an Iron Age development (of especially the 9th and 8th centuries BC), was practised by members of the aristocracies throughout the eastern Mediterranean as early as the 13th century BC, and that the first cavalry can be identified around the same time in Mycenaean Greece and other regions in the eastern Mediterranean. To that end, a range of iconographical, physical-anthropological and archaeological evidence will be reviewed.